MSMEs and the Role of Technology in Achieving Business Sustainability - Sinuhaji, Frans Gidion; Sibarani, Hendra Jonathan; Pakpahan, Victor Maruli (Yayasan Kita Menulis, 2024)
This study investigates the impact of Artificial Intelligence (AI) and Financial Technology (FinTech) on business sustainability among Micro, Small, and Medium Enterprises (MSMEs) in Medan City. Employing an associative research approach, the study utilizes quantitative data derived from both primary and secondary sources. The analysis methods include descriptive statistical analysis and Structural Equation Modeling (SEM). The study's population consists of 100 MSMEs in Medan City, selected through accidental sampling. The findings demonstrate that the adoption of AI and FinTech positively and significantly influences business sustainability. The integration of these technologies enhances operational efficiency, supports faster growth, and ultimately strengthens the sustainability of MSMEs. This research highlights the critical role of digital innovation in driving the development and resilience of small businesses, emphasizing the need for broader adoption of AI and FinTech solutions in the MSME sector to foster long-term growth and competitiveness.